Genetic architecture of the high-inorganic phosphate phenotype derived from a low-phytate mutant in winter wheat - Venegas, Jorge; Guttieri, Mary J.; Boehm, Jeffrey D.; Graybosch, Robert; Bai, Guihua; St. Amand, Paul Craig; Palmer, Nathan; Hussain, Waseem; Blecha, Sarah; Baenziger, P. Stephen (Wiley, 2022)
Phytic acid (myo‐inositol 1,2,3,4,5,6‐hexakisphosphate) in grains and legumes reduces bioavailability and absorption of minerals in the gut via chelation of divalent minerals such as iron and zinc. In wheat (Triticum aestivum L.), a low‐phytate mutant (lpa1‐1), developed by ethyl methanesulfonate mutagenesis, was reported to reduce phytate in wheat grain by up to 35% and to elevate free inorganic phosphate (Pi). Little is known about the genetic architecture conditioning this high‐Pi (HIP) phenotype in wheat. Inheritance of the HIP phenotype was evaluated in three segregating populations developed with the lpa1‐1 derivative A02568WS‐A‐12‐10 as a common parent. Distinct genotypic classes were not identified in these populations. To identify quantitative trait loci (QTL) and develop molecular markers for the HIP phenotype, 171 recombinant inbred lines (RILs) from a winter wheat cross ‘Danby’ × A02568WS‐A‐12‐10 were phenotyped for Pi concentration and genotyped by reduced‐representation sequencing. A total of 1,246 nonredundant, high‐quality single‐nucleotide polymorphisms (SNPs) were used to construct a linkage map spanning 3,272 cM. Two major‐effect QTL were identified on chromosomes 4D and 5A, accounting for 23 and 33% of the total phenotypic variation, respectively. Multiple interval mapping (MIM) identified synergistic additive × additive epistasis between these QTL, and the full MIM model accounted for 54% of the phenotypic variation in grain Pi. Ten candidate genes were identified within or in close proximity to the genomic locations of the QTL, five of which encode proteins within the inositol phosphate metabolism pathway. Site‐specific marker assays were developed for marker‐assisted breeding.